2008
DOI: 10.1126/science.1164271
|View full text |Cite
|
Sign up to set email alerts
|

Stable Prenucleation Calcium Carbonate Clusters

Abstract: Calcium carbonate forms scales, geological deposits, biominerals, and ocean sediments. Huge amounts of carbon dioxide are retained as carbonate ions, and calcium ions represent a major contribution to water hardness. Despite its relevance, little is known about the precipitation mechanism of calcium carbonate, and specified complex crystal structures challenge the classical view on nucleation considering the formation of metastable ion clusters. We demonstrate that dissolved calcium carbonate in fact contains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

132
1,801
12
41

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,442 publications
(2,047 citation statements)
references
References 23 publications
132
1,801
12
41
Order By: Relevance
“…4). Consequently, despite the recent reports of prenucleation clusters (41)(42)(43), liquid-liquid separation (44)(45)(46), and multiphase aggregationbased pathways of calcite formation (41,42,47) in bulk solutions, the results presented here provide strong evidence that the classical theory of nucleation provides a good description of calcite formation on ionized surfaces and that interfacial energy is a useful concept even when critical nuclei are in the nanometer range. Calculations of γ assume rhombohedral nuclei.…”
Section: Significancementioning
confidence: 80%
“…4). Consequently, despite the recent reports of prenucleation clusters (41)(42)(43), liquid-liquid separation (44)(45)(46), and multiphase aggregationbased pathways of calcite formation (41,42,47) in bulk solutions, the results presented here provide strong evidence that the classical theory of nucleation provides a good description of calcite formation on ionized surfaces and that interfacial energy is a useful concept even when critical nuclei are in the nanometer range. Calculations of γ assume rhombohedral nuclei.…”
Section: Significancementioning
confidence: 80%
“…In particular, the schematic Fig. 1 implies a 'classical' nucleation route encompassing a single energy barrier, but thermodynamic control via 3D nano-confinement is also applicable to non-classical crystallization comprising two-step nucleation 29 and pre-critical clusters residing in local energy minima, 30 since it is the ability to obtain (near) stable nuclei of only the stable polymorph, rather than the nucleation pathway, which ensures the thermodynamic control.…”
Section: Manuscript Textmentioning
confidence: 99%
“…According to the conventional theory, nucleation in a homogenous supersaturated solution occurs via stochastic microscopic density fluctuations and a balance between the bulk and surface energy of an emerging phase (Frenkel 1939). However, recent studies indicate that ion-associates such as pre-nucleation clusters and liquid-like phases play vital roles in determining nucleation phenomena associated with several minerals (Bewernitz et al 2012;De Yoreo et al 2015;Dey et al 2010;Gebauer and Cölfen 2011;Gebauer et al 2008Gebauer et al , 2014Jolivet et al 2006;Wallace et al 2013). Potentiometric titration-based studies on CaCO 3 nucleation have identified distinct crowding niches leading to either enhanced or suppressed ion-association .…”
Section: Crowded Solutions and Confinement: Impact On Nucleationmentioning
confidence: 99%
“…This suggests that soluble additives regulating crystal nucleation and growth are mobile within the matrix structure, prior to mineralization. Considering the approximate partial specific volume of early mineral species (0.67 cc/g) (Gebauer et al 2008) and assuming compact morphologies, amorphous phases and pre-nucleation clusters smaller than 1.17 nm can permeate through the excluded volume of the collagen matrix. Infiltration of a collagen fibril by such small calcium carbonate clusters was indeed experimentally observed by Nudelman et al (2010).…”
Section: Mineralization In Matrices and Gelsmentioning
confidence: 99%